The Impact of Human Resources and Social Capital on the Economic Inclusivity of MSMEs with Disabilities in Purworejo Regency (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the effect of human capital and social capital on economic inclusivity among micro, small, and medium enterprises (MSMEs) owned by persons with disabilities in Purworejo Regency. A quantitative approach was employed by distributing questionnaires to 69 respondents who are MSME actors with disabilities. The data were analyzed using validity and reliability tests, multiple linear regression, as well as t-test and F-test with SPSS 26. The results indicate that the research instruments are valid and reliable. Partially, human capital has a positive and significant effect on economic inclusivity, while social capital shows no significant effect. Simultaneously, both variables have a significant influence with a determination coefficient of 11.3%. These findings highlight that the improvement of human capital such as skills and knowledge plays a crucial role in promoting inclusive economic participation among people with disabilities. Meanwhile, social capital still needs to be strengthened to enhance collaboration and access to economic opportunities within the community
Keywords: disability; economic inclusivity; human capital; MSMEs; social capital